Detection Of Metformin Hydrochloride In A Traditionally Used Indian Herbal Drug For Antidiabetic: A Case Report - MANISH KUMAR,; VIVEKANANDA MANDAL,; S. HEMALATHA, (International Journal of Pharma and Bio Sciences, 2011)
In the presented case, we got an herbal medicine in the form of a set of different color pills from local herbal medicinal practitioner. According to the advertisements on monograph, the product contains only herbal ingredients without any adequate declaration of the ingredients and was declared as anti-diabetic formulation. For identification of the ingredients, the pills were analyzed by UV, IR and HPLC spectroscopy. One major ingredient was detected in the herbal pills and was identified as metformin hydrochloride. Quantification by UV spectroscopy yielded 93.1 mg of metformin base, Dissolution study states that 85% of the drug release in 240 min from pills while the Indian Pharmacopoeia reveals that uncoated metformin hydrochloride tablets should release 85 % drug within 45 minutes. This study demonstrates a common problem with herbal medicines, where adulterations with synthetic therapeutic substances can lead to severe side effects and/or potentially fatal interactions with conventional medicines.